Load settlement characteristics of piled rafts in sand - Hong, Hui Min. (2011)
This study investigates the effects of pile numbers, pile length, pile spacing and pile diameters on the load-settlement response of a piled raft in dense sand through model tests. A total of 17 tests were conducted to study how varying the parameters would affect the load-settlement response of piled rafts in which the piles act as settlement reducers. The effects of pile numbers and pile length on the load-settlement response of a piled raft will be covered in detail this paper.Preparation of the sand bed in which the tests were conducted in was an important part of the